Pengaruh Lingkungan Kerja Dan Gaya Kepemimpinan Terhadap Kinerja Pegawai Melalui Mediasi Kepuasan Kerja Pada Badan Pengelola Keuangan Dan Aset Daerah Kabupaten Karangasem - Ni Putu Novia Kristyarini; I Putu Santika; I Made Petrus (Warmadewa Management and Business Journal (WMBJ), 2026)
This study aims to analyze the effect of work environment and leadership style on employee performance through job satisfaction as a mediating variable. The research was conducted at the Regional Financial and Asset Management Agency of Karangasem Regency. The population in this study consists of all 81 employees at BPKAD Karangasem. The sampling technique used is a census or saturated sampling method. The data analysis techniques include validity testing, reliability testing, classical assumption tests, and path analysis. The results indicate that: (1) the work environment has a positive and significant effect on job satisfaction; (2) leadership style has a positive and significant effect on job satisfaction; (3) the work environment has a positive and significant effect on employee performance; (4) leadership style has a positive and significant effect on employee performance; (5) job satisfaction has a positive and significant effect on employee performance; (6) job satisfaction mediates the effect of work environment on employee performance; and (7) job satisfaction does not mediate the effect of leadership style on employee performance at BPKAD Karangasem. Based on these findings, it is suggested that BPKAD Karangasem leaders improve the work environment, leadership style, and job satisfaction in order to enhance employee performance